'Italy's involvement in PSO: between self-interest and the logic of appropriateness'. Issue 2 (3rd April 2019) - Pinto Arena, Maria do Céu
ABSTRACT: What factors shape a state's willingness to get involved in Peace Support Operations (PSO), a notoriously risky and costly activity? Do states contribute personnel out of a desire to support the cosmopolitan values embodied in PSO, or out of self-interested behaviour? Are those decisions based on normative, rule-based motivations, or rather on instrumental calculations of national interest? The end of the Cold War opened up new policy options for decision-makers, with Rome showing a strong determination to be more active in that field. Italy purposefully developed a reputation as a security provider, building, along the process, a distinct external self-identity as a natural 'peace-maker'. Which factors explain Italy's evolution from its early guarded support to UN (United Nations) peacekeeping operations, to its current rate of participation? This article argues that Italy makes instrumental use of PSO to gain international visibility and upgrade its ranking, but its strategic narrative, when addressing the general public, relies on a secondary script that adheres to the rhetoric of cosmopolitan rules that prevail in multilateral settings.